Konseling Kelompok Rational Emotive Behavior Therapy (REBT) dengan Nilai Tafakkur untuk Meningkatkan Kecerdasan Emosional Remaja Putra Panti Asuhan Darul Ihsan Prambanan Yogyakarta (Jurusan Bimbingan dan Konseling Islam, 2020)
This research departs from cases of violence that are rife in adolescents' environment in the form of deviant behavior caused by low emotional intelligence. The purpose of this study was to test the effectiveness of the Rational Emotive Behavior Therapy (REBT) group counseling with the value of Tafakkur to Improve the Emotional Intelligence of the Boys at Darul Ihsan Prambanan Orphanage Yogyakarta. The subjects involved were 14 adolescents in the orphanage, who were then divided into two groups, 7 teenagers in the experimental group and 7 teenagers in the control group. This study uses a quasi-experimental design so that the results of the rational emotive behavior therapy (REBT) group counseling with tafakkur value are effective for improving the emotional intelligence of young men at the Darul Ihsan Muhammadiyah Prambanan Orphanage, where the Z value is -2.371 with a significance level of p = 0.018 which means 0.01 <p <0.05.